Tischlerhandwerk in Herrnhut - Kittler, Albrecht (Unitas Fratrum, 2022)
Joinery has been practised as a trade in Herrnhut since about 1730. By taking over the Böhner workshop, it was possible to establish a large-scale workshop in the newly-built Single Brethren’s House in 1745. Between 1760 und 1790 the joinery workshop in the Brethren’s House blossomed and produced high-quality products. At the beginning of the twentieth century this workshop was given up and other workshops developed in parallel. It was only in the 1930s that the Moravian Church in Herrnhut took up the tradition of the former joinery workshop in the Brethren’s House by establishing a new one. The present Herrnhut Wood Workshop Ltd (Herrnhuter Holzmanufaktur GmbH) is its successor. For decades from 1950 the Moravian Church’s joinery workshop was one of the main suppliers of church furnishings to the Protestant churches in the German Democratic Republic and helped to reduce the shortages of church fittings and furniture. Thanks to the high quality of its workmanship, the firm survived the Socialist era, and after a turbulent period in the 1990s it was able to continue its positive development as part of the Dürninger group of companies.